Substantial Differences in Proanthocyanidin Contents among Ginkgo biloba Leaf Extracts in Herbal Medicinal Products Obtained from the German Market - Germer, Stefan; Ritter, Thomas; Wurglics, Mario (Planta Medica, 2024)
Pharmacologic activity of proanthocyanidins in Ginkgo biloba leaf extract has recently been reported. The objective of the present study was to screen proanthocyanidin contents in herbal medicinal products containing Ginkgo extracts. A recently published HPLC method for quantification of proanthocyanidins in G. biloba leaf extract EGb 761 was adopted to also be suitable for finished herbal medicinal products. The method was applied to 14 products from the German market. For each product, a set of three individual batches was purchased and analyzed. Substantial differences in proanthocyanidins contents were found among distinct products, ranging from 0.30 to 5.86%. The batch-to-batch variability within each product was low. The highest concentrations are in a similar range as, for example, the amount of Ginkgo terpene trilactones specified in the monograph for G. biloba leaf extract in the European Pharmacopeia. Although it has not yet been established whether and to what extent proanthocyanidins contribute to the overall pharmacological or clinical efficacy of Ginkgo extracts, a potential impact on the purported benefits of different contents in proanthocyanidins cannot be ruled out. Quality assessment of different Ginkgo extracts in the future may include proanthocyanidins.
Keywords: Herbal medicinal products; EGb 761; quality; extract characterization; Ginkgo biloba; Ginkgoaceae; Ginkgo biloba leaf extract; proanthocyanidins; PACs; HPLC